1995
DOI: 10.1055/s-2008-1066187
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Continuous Esophageal pH-Metering in Infants with Gastroesophageal Reflux and Apparent Life-Threatening Events

Abstract: Episodes of apnea during the first year of life have been classified with the term "Apparent Life-Threatening Events" (ALTE). Gastroesophageal reflux (GER) has been accepted to be one of the factors which can favor ALTE. The aim of this work is to study the continuous 24 h gastroesophageal pH-metering (fundamentally the Reflux Index [RI] and the Area Under Curve [AUC] parameters in three different periods of time: total pH-metering, pH-metering excluding the first two post-prandial hours, and pH-metering durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…(cce); (4) fibroscopy was performed through both nasal fossa of the child while sitting in the mother's arms without anaesthesia (the optic fibres had been treated with an anaesthetic gel for topical use) and was carried out in order to detect signs of irritation of the digestive airways and imminent signs raising the suspicion of gastropharyngeal-laryngeal reflux (Tables 1-3), whose presence would make the patient a candidate for further diagnostic testing via gastric ultrasonography and oesophageal pHmetry; (5) a gastro-oesophageal ultrasound (US) examination was performed with the stomach filled for 10 min, during which the number of episodes of GER was determined and the duration of stagnation in the oesophagus was evaluated (in the neonatal age group, the US examination was extended to the pyloric valve for the study of hypertrophic pyloric stenosis) [3]; (6) oesophageal pH-metry of long duration (18-24 h) to document the presence of acid-based GER (the probes used in our study had a basic indicator, so that they only showed the episodes of reflux which caused a change in the oesophageal pH, without providing information about the quantity of the reflux; the probes yielded information regarding the frequency of episodes of reflux and the amount of time the oesophagus required to eliminate the refluxed acid material) [5]. When performing oesophageal pH-metry, a relevant issue was the correct position of the oesophageal electrode, which must be positioned 3 cm above the lower oesophageal sphincter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(cce); (4) fibroscopy was performed through both nasal fossa of the child while sitting in the mother's arms without anaesthesia (the optic fibres had been treated with an anaesthetic gel for topical use) and was carried out in order to detect signs of irritation of the digestive airways and imminent signs raising the suspicion of gastropharyngeal-laryngeal reflux (Tables 1-3), whose presence would make the patient a candidate for further diagnostic testing via gastric ultrasonography and oesophageal pHmetry; (5) a gastro-oesophageal ultrasound (US) examination was performed with the stomach filled for 10 min, during which the number of episodes of GER was determined and the duration of stagnation in the oesophagus was evaluated (in the neonatal age group, the US examination was extended to the pyloric valve for the study of hypertrophic pyloric stenosis) [3]; (6) oesophageal pH-metry of long duration (18-24 h) to document the presence of acid-based GER (the probes used in our study had a basic indicator, so that they only showed the episodes of reflux which caused a change in the oesophageal pH, without providing information about the quantity of the reflux; the probes yielded information regarding the frequency of episodes of reflux and the amount of time the oesophagus required to eliminate the refluxed acid material) [5]. When performing oesophageal pH-metry, a relevant issue was the correct position of the oesophageal electrode, which must be positioned 3 cm above the lower oesophageal sphincter.…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, the Strobel formula was used to establish the exact distance in centimetres between the nostril and the lower oesophageal sphincter (height  0.252 + 5). The electrode was positioned in the child's cheek and neck with silk sticking plasters in order to avoid accidental removal [5].…”
Section: Methodsmentioning
confidence: 99%
“…Infants and children with extraesophageal reflux disease (EERD) may present with a wide variety of otolaryngologic signs and symptoms [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The diagnosis of EERD may become challenging due to insufficient clinical history and varying sensitivity and specificity of available diagnostic tests [12].…”
Section: Introductionmentioning
confidence: 99%
“…Children suffering from EERD may present with cough [2], laryngitis [3], recurrent croup [4,5], laryngomalacia [6,7], apparent life threatening event [8], apnea [9], asthma [10], subglottic stenosis [11,12], chronic aspiration, sleep disorders [13], otalgia, and rhinosinusitis [14,15]. The typical symptoms of gastroesophageal acid reflux disease (symptoms or tissue damage caused by esophageal reflux of gastric contents with or without esophageal inflammation) such as heartburn occur uncommonly in patients with EERD [16].…”
Section: Introductionmentioning
confidence: 99%